Performance Evaluation of Tuntang Watershed based on Quantity and Quality of Water - Murtiono, Ugro Hari; Paimin, Paimin (Universitas Muhammadiyah Surakarta, 2016)
The objective of the study was to evaluate the performance of Tuntang Catchment based on water quantity and quality area ranging from its upstream to downstream. The method used to determine the water quantity was by carrying out ground study on water discharge in the dry season (June 2011) in the research site, while the water quality was determined by conducting a laboratory analysis on the samples obtained from the sites in both the rainy and dry season (January and June 2011). The results indicated that the quantity of water discharge in Tuntang River was categorized âgoodâ, although it was utilized for many uses such as irrigation, hydropower, and drinking water. Most of water discharges were mainly supplied from the upstream of Rawa Pening Lake. The water quality determined from the parameters of total dissolved solids, conductivity, pH, phosphate, and nitrate could be classified as âgoodâ, meanwhile, the turbidity and dissolved oxygen were classified as âpoorâ.